Examination of the stigma experiences and needs of individuals with serious mental illness - Gibbons, Carrie Elizabeth (My University, 2008)
Study area : Northwestern Ontario.

This project explores the stigma experienced by individuals with serious mental illness (SMI) and identifies their needs, both met and unmet. This is a somewhat unique approach as the data has been gathered solely from the perspective of individuals with mental illness. Researchers have stated that “the voice of service users is not strongly represented in the literature on stigma (Thornicroft, 2007, p. 153) and further that need has historically been “invariably oriented towards the perceptions of staff rather than those of patients” (Slade, Phelan, Thornicroft, & Parkman, 1996, p. 109). Corrigan and Penn point out that people with mental illness have unique insight into their disease and “excluding their perspective would omit a large and essential body of information” (Corrigan & Penn, 1997, p. 359). Thus, this project provides an important discussion of stigma and needs experienced by people with SMI.
Keywords: Mental health services; Mentally Ill Persons; Stigma (Social psychology)